1990
DOI: 10.1111/j.1399-6576.1990.tb03132.x
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral nutrition in preterm neonates with and without carnitine supplementation

Abstract: The effects of carnitine supplementation on fat and glucose metabolism and carnitine balance were studied in 12 preterm neonates receiving full or partial parenteral nutrition (PN) for 5 to 21 days. The gestational age ranged from 27 to 32 weeks and the birth weight from 790 to 2090 g. The neonates were assigned at random to receive either L-carnitine 10 mg/kg (n = 6) or saline (n = 6). In the carnitine group, increased concentrations in plasma of total and free carnitine were observed. Less than 50% of the gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The normative levels and postnatal changes in plasma carnitine in the preterm neonate are now well characterized [36], [37], [38]. Sick preterm neonates who do not receive carnitine supplementation via the enteral or parenteral route continue to have lower tissue carnitine levels [39], [40], [41], [42] which drop further, and thus may develop a state of relative tissue carnitine deficiency. We hypothesize that tissue carnitine deficiency will have an impact at the molecular level in the developing GI tract.…”
Section: Introductionmentioning
confidence: 99%
“…The normative levels and postnatal changes in plasma carnitine in the preterm neonate are now well characterized [36], [37], [38]. Sick preterm neonates who do not receive carnitine supplementation via the enteral or parenteral route continue to have lower tissue carnitine levels [39], [40], [41], [42] which drop further, and thus may develop a state of relative tissue carnitine deficiency. We hypothesize that tissue carnitine deficiency will have an impact at the molecular level in the developing GI tract.…”
Section: Introductionmentioning
confidence: 99%
“…Using the keywords ''Clinical Trial'' and ''Carnitine'' to search Medline and the Cochrane Database and our our own personal files we found ten randomized clinical trials [8][9][10][11][12][13][14]16,18,19 (Table 5) (s)). 23,24 Whereas three studies showed improved short-term growth, 13,14,24 none of the three published long-term studies 16,18,19 showed any effect of carnitine on growth.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] However, one study using high doses, 300 mmol/kg/day, 15 of L-carnitine supplementation showed increased protein oxidation and decreased weight gain. In 2000, only one randomized controlled study had evaluated the effect of long-term use of carnitine on growth in VLBW infants, 16 and this study had been conducted without sample size analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Improved fatty acid oxidation has been demonstrated if the parenteral nutrition solution is supplemented with L-carnitine. [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Thus the higher LLM index, particularly following the introduction of Intralipid, may reflect a relative carnitine deficiency.…”
Section: Fig 2 Scattergram Of All Llm Index Values (Il and Non-il) mentioning
confidence: 99%